Enhancing Whistleblower Protection Against Corruption Based on Addressing Inadequacies and Enhancing Digital Technology Applications in Vietnam - Nguyen, Hoang Anh; Nguyen, Viet Phuong (Journal of Ecohumanism, 2024)
The significance of protecting whistleblowers in Vietnam has gained substantial attention alongside the anti-corruption efforts. Legislative initiatives aimed at safeguarding whistleblowers have contributed significantly to upholding human rights, citizen rights, and, particularly, the rights of those who expose corruption. This article evaluates the existing legal provisions concerning whistleblower protection against corruption in Vietnam, identifies limitations in their practical implementation, and explores best practices from other countries. Moreover, it proposes innovative approaches to develop whistleblower protection laws and highlights the potential for effectively applying digital technology. Recognizing that digital transformation is not solely a technical solution, but also a socio-technical and politico-social solution, this study emphasizes the need for comprehensive whistleblower protection.